Changes in Perceived Impact of Stroke on Everyday Life over Five Years in a Rehabilitation Sample that Received an Activity of Daily Living Intervention: A Follow-Up Study - Mandana Fallahpour; Gunilla Eriksson; Susanne Guidetti (Medical Journals Sweden, 2022)
Objective: To compare changes in the perceived impact of stroke on everyday life over time in a rehabilitation sample that received a client-centred activities of daily living (CADL) intervention or usual ADL (UADL) intervention. Design: Longitudinal follow-up of a randomized controlled trial. Methods: A total of 145 persons with stroke were assigned into CADL or UADL. Groups were assessed using the Stroke Impact Scale (SIS) at 3 months, 12 months and 5 years post-intervention. Changes in SIS domain scores over time were compared within and between groups. Results: Changes in the impact of stroke over time were not related to which intervention the groups received. There were no significant differences in the SIS domains or stroke recovery between groups at the 3-month, 12-month and 5-year follow-ups. Despite an increased impact of stroke over time in some domains in both groups, both groups perceived a decreased impact of stroke in the Participation domain at 12 months. Perceived participation was sustained at the same level at 12 months as at 5 years in both groups. Conclusion: These findings stress the importance of access to follow-up rehabilitation interventions 1-year post-stroke to enable participation in daily activities. Such follow-up and enablement would support the use of self-management strategies in the performance of persons' valued activities, which might be difficult to perform, due to, for example, impact on hand function or mobility. The results of this study emphasize the importance of prioritizing participation in activities that are meaningful from a personal perspective. LAY ABSTRACT In this study, perceived impact of stroke on everyday life over time was compared among 145 persons with stroke who received the client-centred or usual activities of daily living intervention. They were followed up at 3, 12 months and 5-years post-stroke. No differences were found in the impact of stroke over time between groups. Despite increased impact of stroke (indicating more problems) over time in some areas, the groups perceived decreased impact of stroke (less problems) in their participation at 12 months. Perceived participation was sustained at the same level at 12 months as at 5 years in both groups. Findings stress the importance of access to follow-up rehabilitation interventions one-year post-stroke to enable participation in daily activities, and to support the use of self-management strategies to facilitate participation in valued and meaningful activities that might be difficult due to person's functional limitations.